Commentary: Remote assessments of gait and balance - Implications for research during and beyond Covid-19. Issue 1 (2nd January 2022) - Madhavan, Sangeetha; Sivaramakrishnan, Anjali; Bowden, Mark G.; Chumbler, Neale R.; Field-Fote, Edelle C.; Kesar, Trisha M.
ABSTRACT: The COVID-19 pandemic has disrupted non-essential in-person research activities that require contact with human subjects. While guidelines are being developed for ramping up human subjects research, one component of research that can be performed remotely is participant screening for lower limb function and gait impairments. In this commentary, we summarize evidence-supported clinical assessments that have potential to be conducted remotely in a safe manner, to make an initial determination of the functional mobility status of persons with neurological disorders. We present assessments that do not require complex or costly equipment, specialized software, or trained personnel to administer. We provide recommendations to implement remote functional assessments for participant recruitment and continuation of lower limb neurorehabilitation research as a rapid response to the COVID-19 pandemic and for utilization beyond the current pandemic. We also highlight critical research gaps related to feasibility and measurement characteristics of remote lower limb assessments, providing opportunities for future research to advance tele-assessment and tele-rehabilitation.